Chronic Pediatric Immune Thrombocytopenia Is Not Associated With Herpes Virus Infection Status - Li, Tao; Yan, Gui-ling; Luo, Zhu; Xie, Qi; Lai, Mei-mei; Chen, Zhan-Guo; Zheng, Xiao-Qun (Frontiers in Pediatrics, 2021)
Abstract Background: Immune thrombocytopenia (ITP) is characterized by non-chronic (transient, <12 months) and chronic (≥12 months) decline in the number of platelets. Herpes virus infections have been shown, in many studies, to be associated with the development of ITP. However, it remains unclear whether the herpes virus infection status is associated with the chronic ITP. Methods: We reviewed 480 primary pediatric patients with ITP in the period from January 2017 to December 2019. The prevalence of herpes virus antibodies including the Cytomegalovirus (CMV), Herpes simplex virus 1 (HSV-1), Herpes simplex virus 2 (HSV-2), and Epstein Barr virus were recorded. The levels of serum complement C3 and C4, T (CD3+, CD4+, CD8+), B (CD19+) lymphocytes, and natural killer (CD16+ 56+) cells were also analyzed. Multivariate analysis was used to evaluate the associations between chronic ITP and herpes virus infection status. Results: Compared with non-chronic ITP, patient with chronic had older age (≥ 3 years), low level of hemoglobin and complement C3, and lower probability of CMV and HSV-2 infections (IgM positive; p<0.05). Patients with herpes virus infection had lower serum platelet counts (p<0.001), lower complement C3 levels and lower CD4+/CD8+ cells ratio (p<0.05). Furthermore, platelet counts were positively correlated with CD4+/CD8+ cells ratios (r=0.519; p=0.0078), and negatively correlated with T cells (CD3+: r=-0.458, p=0.0213; CD8+: r=-0.489, p=0.0131). Multivariate analysis showed that age (OR,1.644;95%CI, 1.007~2.684; p=0.047) was an adverse risk factor for chronic ITP and CMV IgM positive (OR,0.241;95%CI, 0.072~0.814; p=0.022) had lower risk of chronic ITP development, while other herpes virus infection status and clinical features were not. Conclusion: Although herpes virus infections were associated with the onset of ITP, our findings indicated that herpes virus infections status might not be a risk factor for chronic ITP.